Highly efficient solution processed blue organic electrophosphorescence with 14 lm/W luminous efficacy - Choulis, Stelios A.; Mathai, Mathew K.; Choong, Vi-En (My University, 2006)
We report highly efficient solution processed blue electrophosphorescent organic light emitting diodes (PHOLEDs) utilizing a phosphorescent dye and a nonconjugated polymer host, molecularly doped with electron transporting molecules. Based on a bilayer device architecture blue PHOLEDs with luminous efficacy of 14 lm/W at luminous efficiency reaching 22 cd/A are demonstrated. Analysis of device performance indicates that this high efficiency is achieved by a combination of improved charge balance and light outcoupling efficiency. Our results demonstrate that simple solution processed devices can have efficiencies similar to those published to date for small molecule multilayer PHOLEDs based on the same emitter
Keywords: Light emitting diodes; Phosphorescence; Product design